Design and development of digital Ramptime current control technique - Hamdan, Daniyal; Borle, L. J.; Lam, E.; Iu, Herbert H. C. (IEEE, 2011)
A new all-digital current control technique is presented in this paper. The current control is based on Ramptime current control technique, where multisampling is chosen as the sampling strategy due to its ability to provide higher accuracy. The resultant current control is called Digital Ramptime current control. The performance of the new current control is compared with the original Ramptime in an active power filter experiment. Results show that with sufficient sampling, the performance of Digital Ramptime is satisfactory.